Magnetofriction—a new concept for shape memory composites. (1st February 2023) - Hermann, S; Muniz, N; Ouisse, M; Hirsinger, L; Chevallier, G
Abstract: This paper introduces a new concept for shape memory based on elastic forces and magnetically induced friction forces in composite materials consisting of magnetoactive elastomers (MAEs). Magnetic attraction forces between two MAEs generate a contact pressure at their interface and the friction allows to maintain stable deformed shapes of the so-called magnetofriction shape memory polymers (MF-SMPs). When the contact is loosened, the friction forces vanish and the elastic forces in each part of the assembly bring the parts back into their initial state where the contact can be established once again. The shape memory effect is studied in three-point bending tests with two stacked MAEs. The global force-displacement relations reveal a hysteretic behavior due to local residual displacements after the test are observed by the help of digital image correlation. The test structure stores up to 25% of the applied displacement. The local contact state (sliding or sticking) is evaluated in different regions of the MF-SMP which gives an insight into the shape memory mechanism magnetofriction. Two methods for the shape-recovery of the MF-SMP by elastic forces in the MAEs are proposed, a manual separation and an air flow at the interface of the MF-SMP, and a comparison of magnetofriction to other shape memory mechanisms is performed.